Rating the energy efficiency of a public building in Sinop city – MT and proposals of adequacy - Bavaresco, Mateus; Sanches, João Carlos Machado; Leão, Érika Fernanda Toledo Borges; Leão, Marlon (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The increase in energy consumption of buildings spurred the creation of mechanisms and strategies that aim principles of energy efficiency. Brazil’s benchmark for evaluating the energy performance of buildings is the Technical Quality Regulation on the Energy efficiency of Com- mercial, Service and Public Buildings (RTQ-C). The Regulation is based on classification of three main aspects: building envelopes, lighting systems and air conditioning systems. There are few labeled buildings in Brazil and the cost to implement the exigencies of RTQ-C in public buildings from Mato Grosso has not been measured yet. This article presented the cost to implement the requirements of energy efficiency in a building from two aspects: the design phase and constructed building (through retrofit). Therefore, we evaluated the characteristics of a public building in the city of Sinop – MT through the prescriptive method. The results showed that increasing the level of overall efficiency of building from “D” to “A”, after building (through retrofit) would cost around 6.10% over the whole value of the building. The oversized systems of lighting and air conditioning was the main factors in the discrepancy between budgets.